Structural basis of transfer RNA processing by bacterial minimal RNase P - Takamasa Teramoto; Takeshi Koyasu; Takashi Yokogawa; Naruhiko Adachi; Kouta Mayanagi; Takahiro Nakamura; Toshiya Senda; Yoshimitsu Kakuta (Nature Communications)
Abstract Precursor tRNAs (pre-tRNAs) require nucleolytic removal of 5′-leader and 3′-trailer sequences for maturation, which is essential for proper tRNA function. The endoribonuclease RNase P exists in diverse forms, including RNA- and protein-based RNase P, and removes 5′-leader sequences from pre-tRNAs. Some bacteria and archaea possess a unique minimal protein-based RNase P enzyme, HARP, which forms dodecamers with twelve active sites. Here, we present cryogenic electron microscopy structures of HARP dodecamers complexed with five pre-tRNAs, and we show that HARP oligomerization enables specific recognition of the invariant distance between the acceptor stem 5′-end and the TψC-loop, functioning as a molecular ruler—a feature representing convergent evolution among RNase P enzymes. The HARP dodecamer uses only five active sites for 5′-leader cleavage, while we identify a 3′-trailer cleavage activity in the remaining seven sites. This elucidation reveals how small proteins evolve through oligomerization to adapt a pivotal biological function (5′-leader processing) and acquire a novel function (3′-trailer processing).